Perinatal Outcomes among Cases of Predicted and Unpredicted Macrosomia - Merita Isaku; Enxhi Vrapi; Tedi Bimbashi; Ina Cala; Kizjona Perdja; Redi Hoxhallari; Astrit Bimbashi (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: Macrosomia is strongly associated with a range of adverse maternal and neonatal outcomes. The effectiveness of screening remains controversial because expecting a macrosomic fetus affects intrapartum management, promoting elective cesarean sections. This study aims to identify differences in outcomes and management among cases with predicted and unpredicted macrosomia.